Faith Behind The Scenes: The Spiritual Life Of Christian Students Of IAKN Kupang Amid The Current Of Social Media - Marniati Pada; Hilno Wesli Malaipen; Jhilianti Marlin Bahan; Lidia Talan; Marcella Maukari; Maher Banu; Andriana Indra Santi Sole (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to explore and deeply understand the spiritual life of Christian students at the Institut Agama Kristen Negeri (IAKN) Kupang amidst the increasingly massive use of social media. The research employs a qualitative approach using a phenomenological method. Data were collected through in-depth interviews, participatory observation, and documentary studies. Informants were selected through purposive sampling, consisting of 10 active students of IAKN Kupang. The results identified three main themes: (1) social media plays a dual role as both an opportunity and a challenge for spiritual life; (2) students experience tension between digital identity and Christian faith commitment; and (3) spiritual adaptation strategies developed by students to maintain faith depth in the digital era. This study concludes that the spiritual life of Christian students at IAKN Kupang is dynamic and contextual, significantly influenced by the intensity and patterns of social media consumption, but can be managed through the formation of solid faith communities and Christian values-based digital literacy.